Construction method and application of portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel
By using CuNi-MOF-based conductive hydrogel to prepare portable electrochemical sensors, the problem of high cost, time-consuming and complex detection of acetaminophen in the prior art is solved, and a fast, accurate and sensitive detection effect is achieved.
Patent Information
- Application Number
- CN202410920782.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-10
- Publication Date
- 2025-03-04
AI Technical Summary
The detection of acetaminophen in the prior art has problems such as high cost, time-consuming detection, and complex operation, and the conductive hydrogel based on MOFs has fewer applications in electrochemical sensors.
CuNi-MOF-based conductive hydrogel is used as electrode material, and CuNi-MOF powder, CHG/CuNi-MOF hydrogel precursor is prepared and dripped onto the screen-printed electrode to form a portable electrochemical sensor for the detection of acetaminophen.
It realizes the rapid and accurate detection of acetaminophen, which has the advantages of good stability, strong anti-interference ability, wide detection range, low detection limit and high sensitivity, and solves the problems of high cost, time-consuming and complex operations in traditional methods.
Smart Images

Figure CN119555764A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of novel nano-functional materials and electrochemical sensors, and in particular to a method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel and application of the portable electrochemical sensor in acetaminophen detection. Background Art
[0002] Acetaminophen, also known as paracetamol, is a fever auxiliary treatment drug. This drug has analgesic, antipyretic, and minimal anti-inflammatory properties and is recognized by experts from various countries. However, once acetaminophen exists in excess in the human body, it will damage the liver and kidneys through hepatotoxicity and nephrotoxicity, and eventually lead to death. Therefore, it is particularly important to propose a convenient, rapid, and accurate method for detecting acetaminophen.
[0003] At present, although there are many methods for the determination of acetaminophen, such as chromatography, fluorescence spectroscopy, ultraviolet spectroscopy, capillary electrophoresis, etc., these methods have disadvantages such as high cost, time-consuming detection, and complex operation. Electrochemical sensors have attracted much attention due to their low cost, fast analysis speed, high sensitivity, convenient operation, and easy miniaturization. The performance of the sensing interface directly determines the electrochemical performance of the sensor.
[0004] Hydrogel is a polymer system formed by cross-linking hydrophilic materials. It has a certain potential to be used in the field of sensing based on the following points: First, the unique three-dimensional network structure can not only increase the electrochemical effective area, but also accelerate the transmission of analytes. Second, it promotes the fixation of nanomaterials and the uniform dispersion in hydrogels, reducing the spatial steric hindrance of nanomaterials. While achieving signal amplification, it prevents the aggregation and change of signals during the detection process. Third, it can carry a large number of materials with different functions, thus being endowed with a variety of properties. Multi-walled carbon nanotubes are a carbon-based material with good conductivity that can be used to enhance the electron transfer ability of composite materials. Metal organic frameworks (MOFs) are porous materials formed by self-assembly of metal ions and organic ligands. It has the advantages of large specific surface area, rich active sites, and good chemical stability. If the above three can be combined, the resulting composite material will definitely show great potential in the construction of electrochemical sensing interfaces.
[0005] At present, the application of MOFs-based hydrogels is mainly concentrated in the fields of drug release, adsorption separation, catalysis, etc., and there is little research in sensing. Even if there is such research, it only stays in the two aspects of colorimetry and fluorescence sensing. There are almost no reports on the application of MOFs-based conductive hydrogels in electrochemical sensors. Summary of the invention
[0006] The purpose of the present invention is to make up for the deficiencies of the prior art and provide a method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel and its use. The prepared hydrogel material has the advantages of large specific surface area, many active sites, good conductivity, etc. The prepared portable electrochemical sensor can be used for the detection of acetaminophen in actual samples.
[0007] In order to achieve the above object, the technical solution of the present invention is as follows:
[0008] A method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel comprises the following steps:
[0009] S1: Preparation of CuNi-MOF powder:
[0010] Copper salt and nickel salt are used as metal sources, trimesic acid is used as an organic ligand, and polyvinyl pyrrolidone is used as a structure directing agent, and are added into a mixed solvent A containing N,N'-dimethylformamide, ethanol and deionized water; after stirring, the mixture is transferred into a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 140-160°C; after the reaction, the mixture is centrifuged and the separated product is washed with ethanol for multiple times; and then dried to obtain CuNi-MOF powder;
[0011] S2: Preparation of CHG / CuNi-MOF;
[0012] Chitosan, CuNi-MOF powder and multi-walled carbon nanotubes are added to an acetic acid aqueous solution, and the components are evenly mixed in the solution to obtain a solution B; cationic guar gum is then added to the solution B, and sodium periodate is added after stirring, and after being fully mixed, a CHG / CuNi-MOF hydrogel precursor is obtained;
[0013] S3: Construction of portable electrochemical sensors:
[0014] The hydrogel precursor is drop-coated on the working area of the screen-printed electrode, so that it can spontaneously gel through the Schiff base self-assembly method; it is naturally dried at room temperature, so that the screen-printed electrode is modified by CHG / CuNi-MOF, and the portable electrochemical sensor is obtained.
[0015] The method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel according to claim 1 is characterized in that: in step S1, the copper salt is one of copper nitrate trihydrate, copper chloride dihydrate and copper sulfate pentahydrate; the nickel salt is one of nickel nitrate hexahydrate, nickel chloride hexahydrate and nickel sulfate heptahydrate; the molar ratio of nickel salt, copper salt and trimesic acid in solution A is 60:12:(4-6).
[0016] Furthermore, in step S1, the polyvinyl pyrrolidone is one of polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K13-18, polyvinyl pyrrolidone K16-18, polyvinyl pyrrolidone K23-27, polyvinyl pyrrolidone K29-32, polyvinyl pyrrolidone K88-96 or polyvinyl pyrrolidone K90.
[0017] Furthermore, in solution A, the mass ratio of nickel salt to polyvinyl pyrrolidone is 5:(2-4); and the mass ratio of deionized water to copper salt is (20-30):1.
[0018] Furthermore, in solution A, the volume ratio of N,N'-dimethylformamide, ethanol and deionized water is 1:1:1.
[0019] Furthermore, the volume fraction of acetic acid in the solution B is 0.4-0.6%; the mass ratio of acetic acid solution, chitosan, multi-walled carbon nanotubes, CuNi-MOF powder, sodium periodate, and cationic guar gum is: (400-600):12:1:2:10:1.
[0020] Furthermore, in step S3, the amount of the hydrogel precursor applied is 4 to 8 μL, and the drying time is 10 to 15 hours.
[0021] The purpose of the prepared portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel is that it can be used to measure the concentration of acetaminophen in a sample.
[0022] When determining the concentration of acetaminophen in a sample, proceed as follows:
[0023] a. Preparation of standard solution: prepare a series of acetaminophen standard solutions of different concentrations;
[0024] b. Before use, place the portable electrochemical sensor in a desiccator to dry and store;
[0025] c. Connecting related devices: inserting the screen-printed electrode of the portable electrochemical sensor into the chip converter, and then connecting them to the electrode clips of the working electrode, indicator electrode and reference electrode, respectively, and then connecting them to the portable mini electrochemical workstation, and finally immersing the screen-printed electrode in the acetaminophen standard solution;
[0026] d. Drawing of working curve: Differential pulse voltammetry (DPV) was used to measure the oxidation peak current response values of acetaminophen standard solutions of different concentrations. The parameters of DPV test were set as follows: initial potential -0.2 V, termination potential 0.6 V, potential increment 0.004 V, amplitude 0.05 V, pulse width 0.2 s, sampling width 0.02 s, pulse period 0.5 s, rest time 2 s, sensitivity 1×10 -6 A / V, deposition potential 0.0V, deposition time 60s; then draw a linear relationship curve with the concentration of acetaminophen as the horizontal axis and the oxidation peak current as the vertical axis;
[0027] e. Detection of acetaminophen in samples: Take several serum samples, dilute the serum samples to 10 times the volume with 0.1M PBS, use DPV to measure the corresponding oxidation peak current at this concentration, and then calculate the corresponding concentration of acetaminophen in the actual sample based on the working curve obtained by the portable electrochemical sensor.
[0028] The beneficial effects of the present invention are as follows:
[0029] (1) The synthesis method of the electrode material of the portable electrochemical sensor provided by the present invention has the advantages of affordable price, convenient operation, low reaction energy consumption, certain universality and industrial application prospects; CuNi-MOF-based conductive hydrogel has the characteristics of large specific surface area, good catalytic performance, good conductivity, etc.
[0030] (2) The portable electrochemical sensor developed by the present invention has the advantages of good stability, strong anti-interference ability, wide detection range, low detection limit, and high sensitivity for the analysis of acetaminophen, which makes it have broad application prospects in many fields.
[0031] (3) Compared with traditional analytical methods (such as high performance liquid chromatography analysis), the portable electrochemical sensor constructed by the present invention, which is similar to a "chip laboratory" system, solves a series of problems existing in acetaminophen detection, such as high cost, time-consuming detection, and complex operation.
[0032] (4) The design concept provided by the present invention, on the one hand, expands the application of MOFs-based conductive hydrogels in the field of electrochemical analysis, and on the other hand, provides a new perspective for relevant workers to design sensing interfaces with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the SEM image of the CuNi-MOF-based conductive hydrogel in Example 1.
[0034] Figure 2 This is the SEM energy spectrum analysis diagram of the CuNi-MOF-based conductive hydrogel in Example 1.
[0035] Figure 3 A is the DPV current response diagram of the portable electrochemical sensor constructed in Example 2 to different concentrations of acetaminophen in a 0.1 M PBS (pH=7.0) buffer solution.
[0036] Figure 3 B is a linear relationship diagram between the acetaminophen concentration and the current response value in Example 2.
[0037] Figure 4 A is a reproducibility test graph of the portable electrochemical sensor constructed in Example 3 for analyzing 200 μM acetaminophen (0.1 M PBS as the electrolyte, pH=7.0).
[0038] Figure 4 B is a repeatability test graph of the portable electrochemical sensor constructed in Example 3 analyzing 200 μM acetaminophen (0.1 M PBS as electrolyte, pH=7.0).
[0039] Figure 4 C is a stability test graph of the portable electrochemical sensor constructed in Example 3 for long-term analysis of 200 μM acetaminophen for 30 days (0.1 M PBS as electrolyte, pH=7.0).
[0040] Figure 4 D is a stability test graph of the portable electrochemical sensor constructed in Example 3 subjected to 60 cycles of analysis of 200 μM acetaminophen (0.1 M PBS as electrolyte, pH=7.0).
[0041] Figure 5 This is the DPV response diagram of the portable electrochemical sensor constructed in Example 4 for detecting 200 μM acetaminophen under the interference of inorganic ions and biomolecules (the concentrations of inorganic ions and biomolecules are both 20 mM, 0.1 M PBS is used as the electrolyte, pH = 7.0). DETAILED DESCRIPTION
[0042] Example 1
[0043] The preparation process of CuNi-MOF-based conductive hydrogel precursor is as follows:
[0044] S1: First, 2.498g copper salt and 0.415g nickel salt were used as metal sources, 0.150g trimesic acid was used as an organic ligand, and 1.500g polyvinyl pyrrolidone was used as a structure directing agent, and added into a mixed solvent A containing N,N'-dimethylformamide, ethanol and deionized water (wherein the volume ratio of N,N'-dimethylformamide, ethanol and deionized water was 1:1:1); after stirring at 900r for 30min, the mixture was transferred to a polytetrafluoroethylene reactor for a hydrothermal reaction at 150°C for 10h; after the reaction, the mixture was centrifuged at 9000r for 5min, and the product was washed with ethanol for several times; the sample was placed in a vacuum drying oven and dried at 65-75°C for 12h to obtain CuNi-MOF powder;
[0045] S2: 0.625 g chitosan, 0.1 g CuNi-MOF and 0.05 g multi-walled carbon nanotubes were added to acetic acid solution (deionized water as solvent), stirred at 1000 r for 3 to 4 h to allow the components to be evenly mixed in the solution to obtain solution B; finally, 0.5 g cationic guar gum was slowly added to solution B, stirred well, and then 0.05 g sodium periodate was added, stirred at 1000 r for 25 to 30 min, and after thorough mixing, a CHG / CuNi-MOF hydrogel precursor was obtained.
[0046] The copper salt is copper nitrate trihydrate; the nickel salt is nickel nitrate hexahydrate;
[0047] The polyvinyl pyrrolidone was polyvinyl pyrrolidone K30;
[0048] In solution A, the molar ratio of nickel salt, copper salt and trimesic acid is 60:12:5;
[0049] The mass ratio of nickel salt to polyvinyl pyrrolidone in solution A is 5:3;
[0050] The mass ratio of deionized water and copper salt in solution A is 25:1 (at room temperature, the density of water is 1.0 g / mL);
[0051] The volume fraction of acetic acid solution in solution B is 0.5%;
[0052] The mass ratio of acetic acid solution to chitosan in solution B is 40:1;
[0053] The mass ratio of acetic acid solution to multi-walled carbon nanotubes in solution B is 500:1;
[0054] The mass ratio of acetic acid solution to CuNi-MOF in solution B is 250:1.
[0055] The mass ratio of cationic guar gum to acetic acid solution is 1:50;
[0056] The mass ratio of sodium periodate to acetic acid solution is 1:500.
[0057] S3: The construction method of the portable electrochemical sensor is as follows:
[0058] The hydrogel precursor was dripped onto the working area of the screen-printed electrode (SPE) using a 1 mL syringe, so that it could spontaneously gel through Schiff base self-assembly. Finally, it was left to dry naturally at room temperature to obtain a screen-printed electrode with a modified working area.
[0059] The amount of hydrogel precursor dropped was 6 μL, and the drying time was 12 h.
[0060] After obtaining the composite hydrogel, SEM analysis was performed, and the results were as follows Figure 1 As shown in Figure 2, it can be seen that the hydrogel presents a typical three-dimensional network structure. Figure 2 It can be seen from the SEM energy spectrum analysis of the CuNi-MOF-based hydrogel that the elemental components of the composite hydrogel are mainly C, N, O, Ni, and Cu, which proves the successful synthesis of the electrode material.
[0061] Example 2
[0062] The acetaminophen portable electrochemical sensor prepared in Example 1 is used to detect acetaminophen in actual samples, and the steps are as follows:
[0063] a. Preparation of standard solution: prepare a series of acetaminophen standard solutions of different concentrations (0.07, 0.1, 0.3, 0.5, 0.7, 1, 3, 5, 7, 10, 30, 50, 70, 100, 300, 500, 700, 1000, 1300, 1500 μM);
[0064] b. Modifying the working area of the screen-printed electrode: as claimed in the method of claim 1, the CHG / CuNi-MOF is modified in the working area of the electrode and is dried and stored in a desiccator before use;
[0065] c. Connect related devices: insert the screen-printed electrode into the chip converter, and then connect it to the electrode clips of the working electrode, indicator electrode and reference electrode respectively, then connect them to the portable mini electrochemical workstation (PalmSens version from the Netherlands), and finally immerse the screen-printed electrode in the test solution (the test solution consists of 10mL of 0.1M PBS with a pH of 7.0 and a certain amount of acetaminophen). All electrochemical tests were performed on the test software (PS touch) in the smartphone. Before the test, connect the portable mini electrochemical workstation and the smartphone via Bluetooth;
[0066] d. Drawing of working curve: Differential pulse voltammetry (DPV) was used to measure the oxidation peak current response values of acetaminophen standard solutions of different concentrations. The parameters of DPV test were set as follows: initial potential -0.2 V, termination potential 0.6 V, potential increment 0.004 V, amplitude 0.05 V, pulse width 0.2 s, sampling width 0.02 s, pulse period 0.5 s, rest time 2 s, sensitivity 1×10 -6 A / V, deposition potential 0.0V, deposition time 60s; then use origin and other drawing software to draw a linear relationship curve with the concentration of acetaminophen as the horizontal axis and the oxidation peak current as the vertical axis;
[0067] e. Detection of acetaminophen: Take several serum samples. All serum samples were provided by the Affiliated Medical College of Yangzhou University (all pre-treated) and stored at -20°C until use. The serum to which a certain amount of acetaminophen standard solution was added was appropriately diluted (10 times) with 0.1M PBS (pH = 7.0) to reduce the matrix effect of the serum sample; then the DPV was used to determine the size of the oxidation peak current corresponding to the concentration, and then the concentration of acetaminophen in the actual sample was calculated based on the working curve obtained by the portable electrochemical sensor.
[0068] Depend on Figure 3 A It can be seen that as the concentration of acetaminophen increases, the peak current also gradually increases. The linear relationship between the two is as follows Figure 3 B. According to the linear fitting results, the regression equation is y = 0.00666C + 0.08621 (R 2 =0.99616). The detection range of the analytical platform is 0.07-1500 μM, the detection limit is 0.023 μM (S / N=3), and the sensitivity is 0.0450 μA·μM·cm -2 It can be seen that the portable electrochemical sensor has the advantages of wide detection range, low detection limit and high sensitivity.
[0069] Example 3
[0070] Reproducibility, Repeatability and Stability Testing of Portable Electrochemical Sensors:
[0071] In order to evaluate the practical performance of the portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel for acetaminophen detection, relevant tests on reproducibility, repeatability and stability were carried out.
[0072] like Figure 4As shown in A, the same sensor was used to perform 7 reproducibility tests on acetaminophen in 0.1 M PBS (pH=7.0) containing 200 μM acetaminophen. The standard deviation (RSD) of the 7 tests was 2.67%.
[0073] like Figure 4 As shown in Figure B, in 0.1M PBS (pH=7.0) containing 200μM acetaminophen, 7 sensors prepared from the same batch were used to perform repeatability tests on acetaminophen. The standard deviation of the 7 tests was 2.94%. The above data prove that the portable analytical platform we developed has good reproducibility and repeatability.
[0074] like Figure 4 As shown in Figure C, the long-term stability of the sensor was studied by monitoring the current response value of 200 μM acetaminophen every 5 days using DPV. After 30 days, the peak current was still 95.3% of the first set of data.
[0075] like Figure 4 As shown in Figure D, the cyclic stability of the sensor was analyzed. After 6 cycles of testing, the signal did not change significantly, and 94.3% of the first 10 cycles was retained. It can be seen that the developed portable electrochemical sensor has excellent stability.
[0076] Example 4
[0077] Anti-interference test of portable electrochemical sensors:
[0078] Common interference substances in serum were selected for testing to evaluate the anti-interference performance of the sensor. Figure 5 As shown. At 100 times the concentration of inorganic ions (K + , Ca 2+ 、Na + Mg 2+ 、Al 3+ , Fe 3+ , Cu 2+ 、Zn 2+ NH4 + 、NO3 - 、CO3 2- , Cl - 、SO4 2- and PO4 3-) and biological molecules (guanine, adenine, cytosine, thymine, hypoxanthine, glutamate, L-cysteine, ascorbic acid, dopamine, heme, chlorophyll, urea, uric acid, creatinine), 200μM acetaminophen was detected by DPV. The data showed that in the presence of the above potential interferents, the current change value was controlled within ±5%, which can be ignored. This shows that the developed portable electrochemical sensor has strong anti-interference ability.
[0079] Example 5
[0080] Analysis of acetaminophen in real samples:
[0081] In order to further evaluate the reliability of the above analysis platform, according to the test steps of claim 7, the spike recovery analysis of acetaminophen in human serum samples (from the Affiliated Hospital of Yangzhou University) was carried out, and the accuracy of the method was evaluated and verified by the recovery rate and relative standard deviation. The constructed portable sensor was used to detect acetaminophen in human serum. The results are shown in Table 1.
[0082] Table 1. Determination of acetaminophen in serum
[0083]
[0084] The data in Table 1 show that in serum samples, the recovery rate of acetaminophen is between 96.40% and 104.27%, and the relative standard deviation is between 2.00% and 2.64%. The experimental data show that the portable electrochemical sensor we constructed has high accuracy in the determination of acetaminophen and can be used for the quantitative analysis of acetaminophen in actual samples.
[0085] Comparative Example
[0086] The results of the portable electrochemical sensor developed in Example 2 for detecting adrenaline were compared with those in Comparative Examples 1-10, and the results are shown in Table 2. Comparative Examples 1-10 were tested using different electrode materials.
[0087] Table 2. Performance comparison of the analytical platform constructed by the present invention and the method for detecting acetaminophen in Comparative Examples 1-10.
[0088]
[0089]
[0090] It can be seen from the data in Table 2 that the analysis platform constructed by the present invention has better detection performance for acetaminophen than the analysis methods in Comparative Examples 1-10.
[0091] In summary, the present invention proposes a low-cost, easy-to-synthesize, and universal method for preparing a CuNi-MOF-based conductive hydrogel precursor with electrochemical activity for acetaminophen. The obtained electrode material has the characteristics of large specific surface area, good catalytic activity, and strong electron transfer ability, and can be further used to construct a portable electrochemical sensor. The experimental results show that the analytical platform has a wide linear range (0.07-1500μM), a low detection limit (0.023μM), and a high sensitivity (0.0450μA·μM·cm -2 ). In addition, the sensor we developed also has good reproducibility, repeatability, stability and anti-interference. In actual sample analysis, it can accurately determine acetaminophen in serum samples. The recovery rate (96.40-104.27%) is also satisfactory. It can be seen that the analytical platform proposed in the present invention has the potential to show application prospects in many fields.
[0092] The present invention is not limited to the above embodiments. In step S1, the copper salt may be one of copper nitrate trihydrate, copper chloride dihydrate and copper sulfate pentahydrate; the nickel salt may be one of nickel nitrate hexahydrate, nickel chloride hexahydrate and nickel sulfate heptahydrate; the molar ratio of nickel salt, copper salt and trimesic acid in solution A is 60:12:(4-6). The polyvinyl pyrrolidone is one of polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K13-18, polyvinyl pyrrolidone K16-18, polyvinyl pyrrolidone K23-27, polyvinyl pyrrolidone K29-32, polyvinyl pyrrolidone K88-96 or polyvinyl pyrrolidone K90. The mass ratio of nickel salt to polyvinyl pyrrolidone in solution A is 5:2-4; the mass ratio of deionized water to copper salt is (20-30):1. The volume fraction of acetic acid in the solution B is 0.4-0.6%; the mass ratio of acetic acid solution, chitosan, multi-walled carbon nanotubes, CuNi-MOF powder, sodium periodate, and cationic guar gum is: (400-600):12:1:2:10:1. In step S3, the amount of the hydrogel precursor dropwise applied is 4-8 μL; and the drying time is 10-15 hours.
Claims
1. A method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel, characterized in that The steps include: S1: Preparation of CuNi-MOF powder: Copper salt and nickel salt are used as metal sources, trimesic acid is used as an organic ligand, and polyvinyl pyrrolidone is used as a structure directing agent, and are added into a mixed solvent A containing N,N'-dimethylformamide, ethanol and deionized water; after stirring, the mixture is transferred into a polytetrafluoroethylene reactor and subjected to a hydrothermal reaction at 140-160°C; after the reaction, the mixture is centrifuged and the separated product is washed with ethanol for multiple times; and then dried to obtain CuNi-MOF powder; S2: Preparation of CHG / CuNi-MOF; Chitosan, CuNi-MOF powder and multi-walled carbon nanotubes are added to an acetic acid aqueous solution, and the components are evenly mixed in the solution to obtain a solution B; cationic guar gum is then added to the solution B, and sodium periodate is added after stirring, and after being fully mixed, a CHG / CuNi-MOF hydrogel precursor is obtained; S3: Construction of portable electrochemical sensors: The hydrogel precursor is drop-coated on the working area of the screen-printed electrode, so that it can spontaneously gel through the Schiff base self-assembly method; it is naturally dried at room temperature, so that the screen-printed electrode is modified by CHG / CuNi-MOF, and the portable electrochemical sensor is obtained.
2. The method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel according to claim 1, characterized in that: In step S1, the copper salt is one of copper nitrate trihydrate, copper chloride dihydrate and copper sulfate pentahydrate; the nickel salt is one of nickel nitrate hexahydrate, nickel chloride hexahydrate and nickel sulfate heptahydrate; the molar ratio of the nickel salt, the copper salt and trimesic acid in solution A is 60:12:(4-6).
3. The method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel according to claim 1, characterized in that: In step S1, the polyvinyl pyrrolidone is one of polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K13-18, polyvinyl pyrrolidone K16-18, polyvinyl pyrrolidone K23-27, polyvinyl pyrrolidone K29-32, polyvinyl pyrrolidone K88-96 or polyvinyl pyrrolidone K90.
4. The method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel according to claim 3, characterized in that: The mass ratio of nickel salt to polyvinyl pyrrolidone in solution A is 5:(2-4); the mass ratio of deionized water to copper salt is (20-30):
1.
5. The method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel according to claim 1, characterized in that: In solution A, the volume ratio of N, N'-dimethylformamide, ethanol and deionized water is 1:1:
1.
6. The method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel according to claim 1, characterized in that: The volume fraction of acetic acid in the solution B is 0.4-0.6%; the mass ratio of acetic acid solution, chitosan, multi-walled carbon nanotubes, CuNi-MOF powder, sodium periodate, and cationic guar gum is: (400-600):12:1:2:10:
1.
7. The method for constructing a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel according to claim 1, characterized in that: In step S3, the amount of the hydrogel precursor dropped is 4 to 8 μL, and the drying time is 10 to 15 hours.
8. Use of a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel according to any one of claims 1 to 7, characterized in that: Used to determine the concentration of acetaminophen in samples.
9. The use of a portable electrochemical sensor based on CuNi-MOF-based conductive hydrogel according to claim 8, characterized in that: To determine the concentration of acetaminophen in a sample, proceed as follows: a. Preparation of standard solution: prepare a series of acetaminophen standard solutions of different concentrations; b. Before use, dry and store the portable electrochemical sensor in a desiccator; c. Connect related devices: insert the screen-printed electrode of the portable electrochemical sensor into the chip converter, and then connect it to the electrode clips of the working electrode, indicator electrode and reference electrode respectively, and then connect them to the portable mini electrochemical workstation, and finally immerse the screen-printed electrode in the acetaminophen standard solution; d. Drawing of working curve: Differential pulse voltammetry was used to measure the oxidation peak current response values of acetaminophen standard solutions with different concentrations. The parameters of DPV test were set as follows: initial potential -0.2 V, termination potential 0.6 V, potential increment 0.004 V, amplitude 0.05 V, pulse width 0.2 s, sampling width 0.02 s, pulse period 0.5 s, rest time 2 s, sensitivity 1×10 -6 A / V, deposition potential 0.0 V, deposition time 60 s; then draw a linear relationship curve with the concentration of acetaminophen as the horizontal axis and the oxidation peak current as the vertical axis; e. Detection of acetaminophen in samples: Take several serum samples, dilute them with 0.1 M PBS, and then use DPV to measure the oxidation peak current corresponding to the concentration. Then, calculate the corresponding concentration of acetaminophen in the actual sample based on the working curve obtained by the portable electrochemical sensor.
Citation Information
Patent Citations
Cationic guar gum / chitosan composite hydrogel and preparation method thereof
CN110628090A
Preparation method and application of gold nanocluster modified hydrogel
CN118304463A
Hydrogel compositions, methods for preparing the same and uses thereof
GB201515296D0
In situ gelling polysaccharide-based nanoparticle hydrogel compositions, and methods of use thereof
US20210361570A1